2009
DOI: 10.1179/jmt.2009.17.3.154
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Applications of Thoracic Spine Thrust Manipulation do not Lead to Tolerance in Patients Presenting with Acute Mechanical Neck Pain: A Secondary Analysis

Abstract: It has been demonstrated that patients receiving mobilization techniques do not exhibit tolerance to repeated applications. However, this phenomenon has not been investigated for thoracic manipulation. Our aim was to determine if patients receiving thoracic thrust manipulation exhibit tolerance to repeated applications in acute mechanical neck pain. Forty-five patients were randomly assigned to two groups. The control group received electro- and thermotherapy for 5 sessions, and the experimental group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(46 citation statements)
references
References 31 publications
0
45
0
1
Order By: Relevance
“…In our study, PPT was assessed bilaterally over the C5-6 zygapophyseal joint, lateral epicondyle, and tibialis anterior muscle, as previously described. [18][19][20][21]46 Although no study has focused on the reliability of PPT over these specific regions, previous studies have determined its reliability to be high (ICC = 0.89-0.92) for PPT measurements at these locations.…”
Section: Pressure Pain Thresholdmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, PPT was assessed bilaterally over the C5-6 zygapophyseal joint, lateral epicondyle, and tibialis anterior muscle, as previously described. [18][19][20][21]46 Although no study has focused on the reliability of PPT over these specific regions, previous studies have determined its reliability to be high (ICC = 0.89-0.92) for PPT measurements at these locations.…”
Section: Pressure Pain Thresholdmentioning
confidence: 99%
“…Although the thoracic thrust manipulation focused on segments T1 to T4, no specific segment was targeted with respect to the application of the thoracic spine thrust manipulation, similar to previous studies. 20,38 …”
Section: Upper Thoracic Spine Thrust Manipulationmentioning
confidence: 99%
“…In a comparative study carried out by Fernandez-delas-Penas et al 19) , a control group received five sessions of electrothermal therapy, and an experimental group received both electrothermal therapy and thoracic manipulation. The groups submitted to manipulation achieved lower pain scores in the first session (acute effect of manipulation: 25% reduction in pain) as well as after five sessions (63% accumulated reduction in pain), thereby demonstrating the efficacy of this technique in both the short and long terms.…”
Section: Discussionmentioning
confidence: 99%
“…Another form of measurement of pain is the patient's visual analogue pain scale (VAS). According to Cleland et al 18) and Fernandes-de-las-penas et al 19) , the VAS is a reliable and valid instrument to assess pain intensity and was selected as the outcome measure based on its ability to detect immediate changes in pain.…”
Section: Introductionmentioning
confidence: 99%
“…4 Few investigators have reported that neck pain remained unchanged or increased immediately following cervical manipulation. 5,6 Further, neck pain has been inversely related to neck ROM. 7 …”
mentioning
confidence: 99%